Interaction between monensin and lipids addition in diets as manipulators of ruminal kinetics and fermentation for methane mitigation in ruminants - Solórzano, Laura Alexandra Romero (2019)
The present study aimed to evaluate the interaction between the addition of monensin and lipids in diets as manipulators of rumen kinetics and fermentation for methane production mitigation in ruminants. The manuscript describes the results of three experiments that evaluated the effect of eight treatments which differed on the lipid source used and the addition or not of monensin sodium. The treatments were: Control (CONT), diet without lipid and monensin inclusion, canola (CAN), soybean (SOY) and sunflower (SUN). The inclusion of lipid sources in the diet was 3.5% of DM as oil. Besides vegetable oils inclusion, each cow in a square daily received 300 mg (approximately 32 mg / kg DM) of sodium monensin (Rumensin® 200, Elanco Saúde Animal, Brazil) during the whole experimental period, delivered twice a day (150 mg at 08h00 and 150 mg at 16h00), mixed with the diet. The objective of the experiment I was to evaluate the effect of diet supplementation with vegetable oils and monensin in cattle on ruminal fermentation, methane production, microbial protein synthesis and total nutrient digestibility in Nellore cows. The experiment II was carried out with the objective to evaluate the effect of diet supplementation with vegetable oils and monensin on ingestive behavior and ruminal kinetics in Nellore cows. In experiment III, the objective was to evaluate the effect of the combination of monensin and vegetable oils on CO2, CH4 and N2O production during the process of anaerobic biodigestion and the potential of biogas production. In experiment I, Methane emission was reduced by SOY treatment in 22.2%. Effect of interaction was observed for total SCFA, where with no monensin inclusion in diets, CAN treatment reduced this variable in 31.52%, when compared with control treatment. Whereas in the presence of monensin, soybean oil potentialized the response, leading to a reduction of 36.97%, of total SCFA. In Experiment II, potential degradability (PD, %) of DM and NDF were reduced, whereas non degradable fraction (Ind, %) of DM and NDF were increased by the addition of lipids in the diet. This was related to kt (%/h) of DM and NDF which decreased with the addition of lipid sources. In experiment III, biogas, methane CH4) and carbon dioxide (CO2) production increased in CAN (21.8, 19.6 and 29.5%, respectively) compared to CONT treatment. Lipid sources in the form of oil, as well as the antagonistic or synergistic effect of the association between monensin and vegetable oils result in changes in ruminal fermentation variables. The present experiment suggests that lipid sources that have been described to decrease enteric CH4 emissions result in increased biogas production and CH4 production in biodigestion process.